PENGARUH PENINGKATAN KEKAKUAN AKIBAT PERBAIKAN KOLOM TERBAKAR DI DAERAH RAWAN GEMPA - Ningrum, Diana (SISTEM Jurnal Ilmu Ilmu Teknik, 2015)
In a rehabilitation of an after-burnt concrete structure, sometime the component dimension is enlarged. One component in a structure that is usually enlarged for the rehabilitation is a column. For the economic reason, the burnt column concrete is chipped out in a small amount and the column dimension is then enlarged. The enlargement indeed increases the vertical bearing capacity of the column. However, the stiffness of the column is also increase. There can be 100 to 200% increase in the column stiffness. In this paper, the influence of stiffness increase in a column to the dynamic response  of a building is investigated. The model is a three story building in which the column stiffness at the second floor is a variable. A model spectrum analysis was carried out by using El Centro 1940 earthquake response spectrum which is commonly used in seismic design. The results show that a 100% increase in column stiffness at the second floor increases the shear forces by 21%, 18% and 18% at the first, second, and third floors, respectively. Moreover, a 200% increase in column stiffness at the second floor increases the shear forces by 27%, 20%, and 21% at the first, second and third floors, respectively. The increase of shear force in a component is always avoided in a seismic design. Therefore, it is hoped that the results can be used to contributed to the development of a code for rehabilitation of an after-burnt concrete column.